2021
DOI: 10.3390/ani11082281
|View full text |Cite
|
Sign up to set email alerts
|

How Has the COVID-19 Pandemic Affected the Way We Access and Interact with the Countryside and the Animals within It?

Abstract: There is growing evidence that the changes in human behaviour resulting from the COVID-19 pandemic have had positive and negative impacts on the natural world. This study used an online survey to explore how the first UK lockdown affected human exercising behaviour, with particular focus on the role of wild and domestic animals. The survey was completed by 308 respondents. There was a significant increase in the frequency that respondents went for walks outdoors during lockdown, in comparison to pre-lockdown l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Second, the shops and amusement activities present in urban parks were closed, removing a major opportunity for people to visit and relax in these spaces. In natural areas, our results match the lower interest and visitation rates seen in national parks globally [12,45], but not the increased rate of use of the countryside for walks, hikes, and other activities [38,39,43]. Souza et al (2021) found a significant difference between countries with increasing visitation like Finland, where national parks are largely visited by citizens, and countries with decreasing visitation like South Africa, where national parks largely attract international visitors.…”
Section: Changes In Activities Following the Covid-19 Pandemicsupporting
confidence: 63%
See 2 more Smart Citations
“…Second, the shops and amusement activities present in urban parks were closed, removing a major opportunity for people to visit and relax in these spaces. In natural areas, our results match the lower interest and visitation rates seen in national parks globally [12,45], but not the increased rate of use of the countryside for walks, hikes, and other activities [38,39,43]. Souza et al (2021) found a significant difference between countries with increasing visitation like Finland, where national parks are largely visited by citizens, and countries with decreasing visitation like South Africa, where national parks largely attract international visitors.…”
Section: Changes In Activities Following the Covid-19 Pandemicsupporting
confidence: 63%
“…Online surveys have been extensively used as a tool to collect data related to the COVID-19 pandemic and the lockdown, as they comply with distancing regulations and facilitate collecting data from more people easily and quickly [22,[37][38][39][40][41]43,51,52].…”
Section: Survey Design and Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, Moscow reported that the majority of residents decreased their GI use, while the majority of residents in Perth maintained their frequency of use. In addition, the included articles differed as to the effect of lockdown restrictions on visitation, with ten reporting both increases and decreases ( [17] , [19] , [30] , [36] , [37] , [47] , [57] , [60] , [89] , [91] ). Seven studies reported that GI use decreased during lockdown ( [7] , [13] , [31] , [40] , [41] , [48] , [49] ) while three studies reported that use increased during lockdown but decreased as restrictions were eased ( [13] , [20] , [29] ), or that GI use increased during school, gym, and entertainment venue closures ( Curtis et al, 2021 ), suggesting that GI was used as a stopgap to replace other activities that resumed as lockdowns eased.…”
Section: Resultsmentioning
confidence: 99%
“…The ongoing course of the disease, and the ever-evolving policy response to it, will likely determine how long-lasting these effects are. The enforced isolation of people during lockdowns has led to increases in pet ownership and activities related to wildlife, such as gardening, hiking, and creating backyard bird feeders [131]. Whether these will enhance the long-term interest in biodiversity among urbanites [132] remains to be seen.…”
Section: Discussionmentioning
confidence: 99%